A corrente aussie apresenta algum efeito na nocicepção e função motora em modelo animal de dor articular inflamatória? - Silva, Mayara Tavares da (2018)
Introduction: Electrical stimulation, a non-pharmacological resource, has been widely used for pain relief. The aussie current has presented analgesic potential effect, however, its form of action is still hypothetical. Objective: to evaluate the effect of aussie current on nociception and motor behavior in an animal model of inflammatory joint pain. Methods: 36 male Wistar rats were used and the inflammation was induced in the knee by intra-articular injection of a mixture of 3% carrageenan and 3% kaolin. The animals, randomly distributed, were separated into six groups: four groups were treated with aussie current with high or low intensity combined with high or low frequency, burst duration of 4 ms and burst frequency of 50 Hz for 20 minutes; negative control group was remained anesthetized during this same period and the positive one was treated with morphine (5 mg/kg), each group consisting of 6 animals. Primary, secondary and thermalv hiperalgesy, as well as the exploratory locomotor activity of the animals were evaluated. A single investigator performed all assessments, in addition to being masked, and the therapist did not interfere in the assessments. The results were expressed as mean ± SEM. Differences between the groups were related by the two-way ANOVA with the post hoc Tukey test. Values of p <0.05 were considered significant. Results: There was a significant reduction of the deep mechanical threshold 24 hours after induction of inflammation when compared to baseline in all groups (p <0.002). No significant differences were observed in the post-treatment evaluations with the aussie current at moments 0h, 2h, 4h, 6h immediately after the first application and after repeated applications for five consecutive days, only the morphine treated group presented reduction of hyperalgesia (p <0.02). Conclusion: the aussie current did not show antinoceptive effect in animal model of inflammatory pain.